The relationship between body mass index and increased airway reactivity based on methacholine challenge test results - Shoshtari, Maryam Haddadzadeh; Malayeri, Hossein Tahmasbian; Bejestani, Hadi Shahrad (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : According to the reports of the United States National Bureau of Statistics regarding the prevalence of obesity among adults and children and also asthma outbreak, the relationship between asthma and obesity in developed countries is taken into consideration. Aim : Relationship between body mass index and increased airway reactivity based on methacholine challenge test results. Material and methods : It was a retrospective cross-sectional study done on 256 patients who were referred to the lung clinic of the Imam Khomeini Hospital of Ahvaz with symptoms of hypersensitivity of the airways. The patients, who had normal spirometry, were examined by the methacholine challenge test and then they were divided in two groups with positive and negative test results. Results : The patients of this study were 12–84 years old and their average age was 36.3 ±12.1 years. Their mean body mass index (BMI) was 28 ±4.7 kg/m 2 in the group with positive methacholine and 26.7 ±4.9 kg/m 2 in the group with negative methacholine (p = 0.04). It was shown that there has been a statistically significant relationship between BMI and positive methacholine challenge test results (apart from confounding effects of other variables). It seems that the positivity rate of methacholine test rises by 1.06 with an increase in BMI by each unit (p < 0.05). Conclusions : According to the results of this study, it can be said that in high BMI there is a statistically significant association between gender (female) and a positive methacholine challenge test result; but there is no statistically significant association between the methacholine dose and BMI.